2021
DOI: 10.3390/jcm10194593
|View full text |Cite
|
Sign up to set email alerts
|

Current State of the Art and Prospects of T Cell-Redirecting Bispecific Antibodies in Multiple Myeloma

Abstract: Multiple myeloma (MM) patients eventually develop multi-drug-resistant disease with poor survival. Hence, the development of novel treatment strategies is of great importance. Recently, different classes of immunotherapeutic agents have shown great promise in heavily pre-treated MM, including T cell-redirecting bispecific antibodies (BsAbs). These BsAbs simultaneously interact with CD3 on effector T cells and a tumor-associated antigen on MM cells, resulting in redirection of T cells to MM cells. This leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…BsAbs are novel immunotherapeutic approaches that are designed to bind antigens on malignant plasma cells and cytotoxic effector cells, such as T-cells and natural killer cells [67,68]. The use of BsAbs early in clinical trials has shown a favorable safety profile and impressive preliminary efficacy in heavily pretreated patients with MM with response rates ranging between 61% and 83% [67][68][69]. However, CRS and neurotoxicity have been reported and resistance mechanisms were found to be related to the following: tumor-related features, T-cell characteristics, and impact of components of the immune suppressive tumor microenvironment [66,69].…”
Section: Bispecific Antibodies (Bsabs)mentioning
confidence: 99%
See 1 more Smart Citation
“…BsAbs are novel immunotherapeutic approaches that are designed to bind antigens on malignant plasma cells and cytotoxic effector cells, such as T-cells and natural killer cells [67,68]. The use of BsAbs early in clinical trials has shown a favorable safety profile and impressive preliminary efficacy in heavily pretreated patients with MM with response rates ranging between 61% and 83% [67][68][69]. However, CRS and neurotoxicity have been reported and resistance mechanisms were found to be related to the following: tumor-related features, T-cell characteristics, and impact of components of the immune suppressive tumor microenvironment [66,69].…”
Section: Bispecific Antibodies (Bsabs)mentioning
confidence: 99%
“…Various clinical trials are currently evaluating combining BsAbs with other agents, such as CD38 monoclonal antibodies, and immunomodulatory agents such as pomalidomide to further improve the duration and depth of responses [69]. Together with CAR T-cells, BsAbs represent a new dimension in precision medicine in MM [68].…”
Section: Bispecific Antibodies (Bsabs)mentioning
confidence: 99%
“…Results from the phase 1/2 study of teclistamab in triple-class exposed, relapsed disease (N = 150) showed promising outcomes, with an ORR of 62% and 9-month PFS of 58.5% [57,58]. GPRC5D is an orphan G protein-coupled receptor expressed at significantly higher levels on myeloma cells compared with normal plasma cells targeted by the talquetamab bispecific antibody, which has shown promise in early studies [59]. Fc receptor-homolog 5 (FcRH5) is a type I membrane protein expressed on B cells and plasma cells, and is found on myeloma cells with near 100% prevalence.…”
Section: Promising Investigational Options Other Bcma-targeted Therapiesmentioning
confidence: 99%
“…Cytokine release syndrome (CRS) is a known side effect of immunotherapy, including chimeric antigen receptor (CAR)-T cell therapy, T cell redirecting bispecific antibodies, and bispecific T cell engagers. 1,2 CRS can be mild to life-threatening and requires careful monitoring and management. 2 The anti-interleukin (IL)-6 receptor antibody tocilizumab is approved in the US and other regions to treat severe or life-threatening CRS induced by CAR-T cell therapy.…”
Section: Introductionmentioning
confidence: 99%